Exploring the chemical space of 1, 2, 3-triazolyl triclosan analogs for discovery of new antileishmanial chemotherapeutic agents. Issue 1 (5th November 2020) - Fernández de Luco, Julia; Recio-Balsells, Alejandro I.; Ghiano, Diego G.; Bortolotti, Ana; Belardinelli, Juán Manuel; Liu, Nina; Hoffmann, Pascal; Lherbet, Christian; Tonge, Peter J.; Tekwani, Babu; Morbidoni, Héctor R.; Labadie, Guillermo R.
Abstract : A collection of 37 triazolyl-triclosan derivatives were prepared as possible antileishmanial drugs. The InhA ortholog in Leishmania donovani was proposed as a putative druggable target. Abstract : Triclosan and isoniazid are known antitubercular compounds that have proven to be also active against Leishmania parasites. On these grounds, a collection of 37 diverse 1, 2, 3-triazoles based on the antitubercular molecules triclosan and 5-octyl-2-phenoxyphenol (8PP) were designed in search of novel structures with leishmanicidal activity and prepared using different alkynes and azides. The 37 compounds were assayed against Leishmania donovani, the etiological agent of leishmaniasis, yielding some analogs with activity at micromolar concentrations and against M. tuberculosis H37Rv resulting in scarce active compounds with an MIC of 20 μM. To study the mechanism of action of these catechols, we analyzed the inhibition activity of the library on the M. tuberculosis enoyl-ACP reductase (ENR) InhA, obtaining poor inhibition of the enzyme. The cytotoxicity against Vero cells was also tested, resulting in none of the compounds being cytotoxic at concentrations of up to 20 μM. Derivative 5f could be considered a valuable starting point for future antileishmanial drug development. The validation of a putative leishmanial InhA orthologue as a therapeutic target needs to be further investigated.